2021
DOI: 10.1017/pab.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

The geography of phylogenetic paleoecology: integrating data and methods to better understand biotic response to climate change

Abstract: Deeper knowledge about how species and communities respond to climate change and environmental gradients should be supported by evidence from the past, especially as modern responses are influenced by anthropogenic pressures, including human population growth, habitat destruction and fragmentation, and intensifying land use. There have been great advances in modeling species’ geographic distributions over shallow time, where consideration of evolutionary change is likely less important due to shorter time for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 151 publications
(183 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that concentration increase of greenhouse gas emissions may result in a sustained increase [13]. Changes in the spatial and temporal pattern of climate may lead to changes in the geographical distribution of rare and endangered species, thus threatening their original habitats [14,15]. Therefore, a systematic verification of the geographical distribution pattern of rare and endangered species under climate change scenarios can effectively protect the habitat of rare and endangered species as well as the authenticity of ecological system [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that concentration increase of greenhouse gas emissions may result in a sustained increase [13]. Changes in the spatial and temporal pattern of climate may lead to changes in the geographical distribution of rare and endangered species, thus threatening their original habitats [14,15]. Therefore, a systematic verification of the geographical distribution pattern of rare and endangered species under climate change scenarios can effectively protect the habitat of rare and endangered species as well as the authenticity of ecological system [16].…”
Section: Introductionmentioning
confidence: 99%
“…In Oscillayers, benthic δ 18 O records are first merged with Community Climate System Model Version 4 LGM-model simulations (Gent et al, 2011), and then extrapolated across the Plio-Pleistocene using the δ 18 O data. Oscillayers data shows a reasonably good match with independent time-slice GCM simulations (Gamisch, 2019) and has been used in several studies covering different time spans (Hölzchen et al, 2022;Lawing, 2021;McGuire & Lauer, 2020). ) is indicated by a closed blue circle.…”
Section: Observation and Simulation Datamentioning
confidence: 87%
“…Our interpretation of deep-time biogeography is complicated by lower spatial and temporal occurrences in the fossil record, fewer models of paleoclimate, and the need to consider evolutionary change. Lawing (2021) discussed the progression of SDMs and ENMs, including the application of climate envelope models to the fossil record, and described a framework for paleophylogeographic SDMs. This framework incorporates phylogenetic relatedness, fossil occurrences, and paleoclimate from general circulation models in deep time to infer past hotspots of species diversification and past geographic responses of species to environmental change.…”
Section: Ecological Niche Modeling and Species Distribution Modellingmentioning
confidence: 99%
“…Phylogenetic comparative methods (PCMs) are used to quantify the diversification of clades, evolutionary patterns of traits, and species biogeography. Although PCMs are most often used at the macroevolutionary level, an increasing number of researchers have recognized the advantages of applying these methods to conservation (Condamine et al 2013, Lamsdell et al 2017, Lawing 2021, Pyron & Pennell 2022. For instance, using phylogenies to estimate speciation and extinction rates and clade age can help us understand the vulnerability and evolutionary potential of species or clades (Condamine et al 2013, Pyron & Pennell 2022.…”
Section: Macroevolutionary Modelingmentioning
confidence: 99%